Production of cement-bonded particleboards from poplar (Populus euramericana cv. „I 214“) - Tibor Alpár (University of Zagreb, Faculty of Forestry and Wood Technology, 2009)
The aim of our research was to develop a method for producing cement-bonded particleboards (CBPB) at the lowest possible cost. There are two possibilities for using poplar as raw material, and for using a new combination of chemicals as additives, the solution of calcium-chloride and calcium-formate instead of water glass. The present technology uses exclusively Scots pine (Pinus sylvestris) chips, which is getting increasingly expensive. The price of the new additive is lower, as well as the price of poplar compared to Scots pine. As a result of our research, the costs of CBPB production can be reduced. Physical and mechanical properties of the boards usually improved rather than deteriorated.